2020
DOI: 10.35371/aoem.2020.32.e9
|View full text |Cite
|
Sign up to set email alerts
|

Association between use of humidifier disinfectant and allergic rhinitis in Korean children: a cross-sectional study based on the eighth Panel Study on Korean Children (PSKC)

Abstract: Background: Rhinitis was the most frequently diagnosed disorder among users of humidifier disinfectants (HDs). The aim of our study was to investigate on the relationship between allergic rhinitis (AR) and HD uses. Methods: Our study used the data from the eighth Panel Study on Korean Children; a total of 1,540 participants were enrolled. The χ 2 test and multiple logistic regression analyses were conducted to debunk the association between AR and HD uses. Results: In our analysis, odds ratios (ORs) of doctor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Recently, the Panel Study on Korean Children reported a correlation between the use of HDs and diagnosis of allergic rhinitis, 12 24 and also revealed a correlation with upper respiratory disease, which is a precursor to lower respiratory disease. 12 In addition to respiratory disease, there have also been experimental results demonstrating the possibility of systemic toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Panel Study on Korean Children reported a correlation between the use of HDs and diagnosis of allergic rhinitis, 12 24 and also revealed a correlation with upper respiratory disease, which is a precursor to lower respiratory disease. 12 In addition to respiratory disease, there have also been experimental results demonstrating the possibility of systemic toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…For group 1, studies published on humans, a total of 49 articles were selected ( Table 2 ). 1 2 3 4 5 6 7 9 10 11 12 13 14 17 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 The suspicion that humidifier disinfectant might be a cause of lung damage was suggested in 2011. Studies in international journals began to appear in 2013.…”
Section: Resultsmentioning
confidence: 99%
“…28 Overall, annual humidifier disinfectant sales showed high correlations with the concentration and number of HDLI cases. 29 30 31 Respiratory diseases such as idiopathic interstitial pneumonia, 17 bronchitis and allergic rhinitis, 32 33 and asthma 34 have been described in human studies on non-HDLI diseases. Leem et al 35 proposed that these disease types should be grouped and named humidifier disinfectant-related respiratory syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, allergic rhinitis has shown interesting increase in prevalence [ 6 ]. Humidifier disinfectant use is also a risk factor for allergic rhinitis; demonstrations in rat experiments showed degeneration of the normal nasal epithelium [ 9 ]. However, with the decreasing use of humidifier disinfectants, the prevalence of allergic rhinitis has increased while that of asthma has decreased, which defies the concept of a one-airway disease [ 6 ].…”
mentioning
confidence: 99%